Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2009
DOI: 10.1145/1518701.1518853
|View full text |Cite
|
Sign up to set email alerts
|

Understanding how and why open source contributors use diagrams in the development of Ubuntu

Abstract: Some of the most interesting differences between Open Source Software (OSS) development and commercial colocated software development lie in the communication and collaboration practices of these two groups of developers. One interesting practice is that of diagramming. Though well studied and important in many aspects of co-located software development (including communication and collaboration among developers), its role in OSS development has not been thoroughly studied. In this paper, we report our investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 14 publications
3
14
0
Order By: Relevance
“…This was also found by Cherubini et al and Yatani et al [3,20], and we did not observe noticeable differences from their findings. Thus, we decided not to further analyze this scenario.…”
Section: Enhancing One's Own Understandingsupporting
confidence: 90%
See 4 more Smart Citations
“…This was also found by Cherubini et al and Yatani et al [3,20], and we did not observe noticeable differences from their findings. Thus, we decided not to further analyze this scenario.…”
Section: Enhancing One's Own Understandingsupporting
confidence: 90%
“…Yatani et al examined how Ubuntu contributors used diagrams in their project [20]. They found that Ubuntu contributors occasionally used diagrams for five of the nine scenarios defined by Cherubini et al [3].…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations